Adoption of Halal Supply Chain among Malaysian Halal Manufacturers: An Exploratory Study - Abdul Hafaz, Ngah; Yuserrie, Zainuddin; Thurasamy, Ramayah (Elsevier Ltd., 2014)
The paper attempts to have an overview regarding Halal supply chain adoption among Halal manufacturers in Malaysia for transportation and warehouse activities from the perspective of Halal supply chain service providers. Halal supply chain is created by Halal logistics service providers to meet the demand from Halal manufacturers in order to maintain the Halal integrity for Halal products. Halal products are not confirm Halal if manufacturers are not adopting Halal supply chain services. This is an exploratory study with a series of face to face interviews were conducted with three Halal supply chain service providers. The results showed that adoption rates for Halal transportation and Halal warehouse are still relatively low. Respondents also mentioned that there are various barriers that may impede Halal manufacturers from adopting Halal transportation and Halal warehouse to run their products. In sum, this paper generates ideas for researchers to conduct other researches to gain more knowledge regarding Halal supply chain services adoption.